Profitability and profit risk analysis of corn farming in District of Utan, Sumbawa Regency: A cross-sectional study. Issue 1 (1st December 2022) - Yakin, Addinul; Putri, Hera Fatira; Amiruddin,
Abstract: The planting area of corn on Sumbawa Island continues to increase, although deforestation is leading to environmental disasters. This raises the question of whether this commodity is profitable enough for farmers and how high the level of profit risk is. Research has been carried out using multi-stage random sampling. This research was conducted in the district of Utan as, one of the high planting areas and amount of corn production in Sumbawa Regency. Then, 3 (three) villages out of 9 (nine) villages in the district were determined as samples by purposive sampling method representing villages with different levels of productivity. Pukat Village for the highest productivity, Orong Bawa Village for medium productivity, and Stowe Brang Village for low productivity with total respondents of 30 people. The result of the study showed that corn farming provides high profitability but with a relatively high-profit risk. This risk is partly due to the variation and relatively high production costs, especially for labor and water machine rent due to different financial capacities among farmers. The limited and scarce availability of seeds, fertilizers, and water, as well as weather uncertainty, were also considered responsible for the high-profit risk of corn farming. It is desirable to continuously provide financial assistance and/or subsidized inputs for farmers to ensure that they have enough money/funding to run good corn farming practices.